Exchange rate pass-through and inflation dynamics in Tunisia: A Markov-Switching approach - Rim Khemiri; Mohamed Sami Ben Ali (Kiel Institute for the World Economy (IfW), 2012)
This paper studies the effect of exchange rate pass-through on inflation in Tunisia over the period 2001-2009. The authors' objective is to track inflation regimes for the Tunisian economy and to forecast its determinants. Using a Markov-switching approach, the authors identified two main regimes for inflation in Tunisia over this period: a low and stable inflation regime associated with a low pass-through level, and a high inflation regime associated with a high pass-through level. In order to highlight the mechanisms underlying shifts in inflation regimes, the authors used a time-varying probabilities approach and identified a set of variables to assess their effect on inflation in Tunisia. The results show that the price level decreases in response to an increase in interest rates. Along with this, the empirical results provide strong evidence that industrial production indices have a negative and significant effect in increasing the probability to stay in an inflationary regime and a high pass-through level. In addition, the results show robust supports to suggest that the imports increase the probability to stay in a high inflation regime and a high pass-through level. However, exports increase the probability to stay in a low inflation regime and a low pass-through level.
Keywords: F3; F4; G15; 330; Pass-through; inflation; Markov switching; economic fundamentals; Exchange Rate Pass-Through; Inflation; Schätzung; Tunesien